Interferon-β Delivery via Human Neural Stem Cell Abates Glial Scar Formation in Spinal Cord Injury. Issue 12 (December 2013) - Nishimura, Yusuke; Natsume, Atsushi; Ito, Motokazu; Hara, Masahito; Motomura, Kazuya; Fukuyama, Ryuichi; Sumiyoshi, Naoyuki; Aoki, Ichio; Saga, Tsuneo; Lee, Hong J.; Wakabayashi, Toshihiko; Kim, Seung U.
Glial scar formation is the major impedance to axonal regrowth after spinal cord injury (SCI), and scar-modulating treatments have become a leading therapeutic goal for SCI treatment. In this study, human neural stem cells (NSCs) encoding interferon-β (INF-β) gene were administered intravenously to mice 1 week after SCI. Animals receiving NSCs encoding IFN-β exhibited significant neurobehavioral improvement, electrophysiological recovery, suppressed glial scar formation, and preservation of nerve fibers in lesioned spinal cord. Systemic evaluation of SCI gliosis lesion site with lesion-specific microdissection, genome-wide microarray, and MetaCore pathway analysis identified upregulation of toll-like receptor 4 (TLR4) in SCI gliosis lesion site, and this led us to focus on TLR4 signaling in reactive astrocytes. Examination of primary astrocytes from TLR4 knockout mice, and in vivo inhibition of TLR4, revealed that the effect of IFN-β on the suppression of glial scar formation in SCI requires TLR4 stimulation. These results suggest that IFN-β delivery via intravenous injection of NSCs following SCI inhibits glial scar formation in spinal cord through stimulation of TLR4 signaling.